Research on outlier removal method for flight data of helicopter based on wavelet analysis - Wang, Shicheng; Wang, Ling; Cheng, Yajie; Liu, Peili (Proceedings of SPIE, the international society for optical engineering, 2025)
The flight data recording system records important parameter data during helicopter flight and is a key system to ensure helicopter flight safety. The recorded flight data is inevitably subject to various interferences and even outliers. This article proposes a method based on wavelet analysis for outlier removal in flight data. The actual data processing results show that this method can effectively remove outlier points, and the effect is very obvious.